Evaluation of regular and decaffeinated (un)roasted coffee beans based on antioxidant capacity and total phenolic content - Klikarová, Jitka; Řeháková, Barbora; Česlová, Lenka (University of Pardubice, 2023)
In this study, the effect of coffee beans processing (decaffeination and roasting) on their antioxidant capacity and total phenolic content has been investigated. In a total of 64 regular as well as decaffeinated (un)roasted coffee samples, these characteristic parameters were determined spectrophotometrically using the DPPH free-radical method and the Folin-Ciocalteu assay. While the total phenolic content remained unchanged regardless of the processing method used, the antioxidant capacity of the samples varied depending on their treatment being affected mainly by the decaffeination procedure chosen.
Keywords: coffee beans; antioxidant capacity; DPPH; total phenolic content; Folin-Ciocalteu reagent